Devising and validating a headache diary in a series of patients with chronic daily headache from Colombia - Gabriel F Torres; Martha I. Otálvaro; Juan C. Vargas; Yulexi Castellanos; Jeimy Xiomara García; Javier D. Triana; Cesar A. Forero; Carlos D. Guevara; Rodrigo Pardo (Arquivos de Neuro-Psiquiatria, 2012)
OBJECTIVE: To devise and test the reliability and validity of a brief headache diary in a series of Colombian patients with chronic daily headache. METHODS: The study was designed in five stages: selection of domains (group of patients and experts); initial devising of the items (writing group); identification of non-understandable items (n=20); assessment of internal consistency (n=100); assessment of validity and assessment of sensitivity to change during seven consecutive days (n=25, 175 observations). RESULTS: Five domains were selected: headache presence, severity and length of pain, analgesics intake, and missing workdays. The headache diary is internally consistent (≈75% of rotated variance), correlates with the medical interview (Spearman's rho and Kendall's tau over 0.8 for each domain) and it has an adequate and stable sensitivity and specificity (82 to 96%). CONCLUSIONS: This headache diary is a reliable and valid instrument and represents the most important features affecting Colombian patients with chronic daily headache.